New thermodynamic activity-based approach allows predicting the feasibility of glycolysis - Greinert, Thorsten; Vogel, Kristina; Maskow, Thomas; Held, Christoph (Technische Universität Dortmund, 2021)
Thermodynamic feasibility analyses help evaluating the feasibility of metabolic pathways. This is an important information used to develop new biotechnological processes and to understand metabolic processes in cells. However, literature standard data are uncertain for most biochemical reactions yielding wrong statements concerning their feasibility. In this article we present activity-based equilibrium constants for all the ten glycolytic reactions, accompanied by the standard reaction data (standard Gibbs energy of reaction and standard enthalpy of reaction). We further developed a thermodynamic activity-based approach that allows to correctly determine the feasibility of glycolysis under different chosen conditions. The results show for the first time that the feasibility of glycolysis can be explained by thermodynamics only if (1) correct standard data are used and if (2) the conditions in the cell at non-equilibrium states are accounted for in the analyses. The results here will help to determine the feasibility of other metabolisms and to understand metabolic processes in cells in the future.
Scientific reports;11
Keywords: Biocatalysis; Biochemistry; Biosynthesis; Catalysis; Chemical engineering; Enzymes; Physical chemistry; Chemical synthesis; 660